1996
DOI: 10.1002/(sici)1097-4598(199601)19:1<74::aid-mus10>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies of the duplication form of Charcot‐Marie‐Tooth polyneuropathy

Abstract: This study presents a longitudinal comparison of motor nerve conduction velocities (MCVs) in patients with Charcot-Marie-Tooth type 1A with proven duplication of a segment of chromosome 17pl1.2p12. Results were compared for 8 CMTIA duplication patients from one family whose MCV measurements were taken 22 years apart (1967 and 1989). Measurements from a total of seven median motor and five peroneal motor MCVs were compared. Median MCVs showed a slight reduction that averaged 2.2 m/s, and peroneal MCVs showed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Because myelination proceeds in humans from 5 months of gestation until the age of about 14 years, 15 this period is presumably the most vulnerable window to PMP22 duplication. Such a pathological evolution agrees with the electrophysiological findings in the present series and in other crosssectional 3,14 and longitudinal studies 16 ; progressing age worsens neither the MNCV slowing nor the decreased compound motor action potential ampli- tudes. Whereas the electrophysiological measures in the duplicated form of CMT1A do not progress with age, the clinical deficits apparently do.…”
Section: Discussionsupporting
confidence: 93%
“…Because myelination proceeds in humans from 5 months of gestation until the age of about 14 years, 15 this period is presumably the most vulnerable window to PMP22 duplication. Such a pathological evolution agrees with the electrophysiological findings in the present series and in other crosssectional 3,14 and longitudinal studies 16 ; progressing age worsens neither the MNCV slowing nor the decreased compound motor action potential ampli- tudes. Whereas the electrophysiological measures in the duplicated form of CMT1A do not progress with age, the clinical deficits apparently do.…”
Section: Discussionsupporting
confidence: 93%
“…It is of interest that, although these findings have already been noted in previous reports [2,11], the current notion is that NCV does not change significantly through the life of CMT1A patients [7][8][9]. Birouk and colleagues found in their large sample of CMT1A patients that NCV increased with age and they interpreted the more evident lower NCV in younger patients as an expression of early diagnosis in younger CMT1A patients due to their more severe symptoms [2].…”
Section: Discussionmentioning
confidence: 70%
“…In CMT1A, MNCV is uniformly reduced in all nerves and values <38 m/s are highly diagnostic [2,3]. This electrophysiological hallmark, fully penetrant since the first years of life [4][5][6], remains fairly stable through life [7][8][9] and does not correlate with disability, whereas compound motor action potential (CMAP) amplitude that is a surrogate marker of axonal degeneration does [3].…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a number of recent clinical and experimental studies (Killian et al 1996;Garcia et al 1998;Robertson et al 1999;Sahenk 1999;Sancho et al 1999) of the common autosomal dominant demyelinating forms of Charcot-Marie-Tooth (CMT) disease have indicated that the neurological deficit in demyelinating neuropathies is related to axonal loss, rather than to demyelination per se. The neuropathologic features of HMSNL make it impossible to attribute the primary defect to either Schwann cells or neurons, and they strongly suggest that impairment of Schwann cell-axonal interaction is a major component of the pathogenesis of this disease.…”
Section: Introductionmentioning
confidence: 99%